Analysis of the “Freedom of the Word” Project as a generator of literacy practices in contexts of confinement, vulnerability and social exclusion - Moscoso Carbonel, Emilia (2024)
The main objective of this article is to analyze the project “Freedom of the Word” as a generator of literacy practices in contexts of confinement, vulnerability and social exclusion. To meet this objective, two specific objectives are proposed: the first, to examine the dynamics of the project in its implementation within these contexts; and the second, to evaluate the logical framework methodology used in the project and its impact on the generation of literacy practices. The approach adopted is qualitative, based on two methods: theoretical-conceptual analysis and documentary treatment of information. It is concluded that both the dynamics and the methodology of the logical framework of the project “Freedom of the Word” contribute to the “repressive-ideological” function of the prison regime, by simplifying and reducing the complexity of the social realities of the participants. However, the project also plays a therapeutic role, allowing inmates to cope with confinement in a healthier way, to express their thoughts, memories, emotions and feelings, to develop their creative skills, to recognize new possibilities for change and to construct new meanings and practices that enhance their capacity for agency within their context.